Effect of metformin therapy on circulating amino acids in a randomized trial: the CAMERA study. Issue 11 (3rd March 2016) - Preiss, D.; Rankin, N.; Welsh, P.; Holman, R. R.; Kangas, A. J.; Soininen, P.; Würtz, P.; Ala‐Korpela, M.; Sattar, N.
Abstract: Aims: To investigate whether metformin therapy alters circulating aromatic and branched‐chain amino acid concentrations, increased levels amino acid concentrations, increased levels of which have been found to predict Type 2 diabetes. Methods: In the Carotid Atherosclerosis: Metformin for Insulin Resistance (CAMERA) study (NCT00723307), 173 individuals without Type 2 diabetes, but with coronary disease, were randomized to metformin ( n =86) or placebo ( n =87) for 18 months. Plasma samples, taken every 6 months, were analysed using quantitative nuclear magnetic resonance spectroscopy. Ten metabolites consisting of eight amino acids [three branched‐chain (isoleucine, leucine, valine), three aromatic (tyrosine, phenylalanine, histidine) and two other amino acids (alanine, glutamine)], lactate and pyruvate were quantified and analysed using repeated‐measures models. On‐treatment analyses were conducted to investigate whether amino acid changes were dependent on changes in weight, fat mass or insulin resistance estimated using homeostasis model assessment (HOMA‐IR). Results: Tyrosine decreased [−6.1 μmol/l (95% CI −8.5, ‐3.7); P <0.0001], while alanine [42 umol/l (95% CI 25, 59); P <0.0001] increased in the metformin‐treated group compared with the placebo‐treated group. Decreases in phenylalanine [−2.0 μmol/l (95% CI −3.6, −0.3); P =0.018] and increases in histidine [2.3 μmol/l (95% CI 0.1, 4.6); P =0.045] were also observed in the metformin group, although these changes were less statistically robust. Changes in these four amino acids were not accounted for by changes in weight, fat mass or HOMA‐IR values. Levels of branched‐chain amino acids, glutamine, pyruvate and lactate were not altered by metformin therapy. Conclusions: Metformin therapy results in a sustained and specific pattern of changes in aromatic amino acid and alanine concentrations. These changes are independent of any effects on weight and insulin sensitivity. Any causal link to metformin's unexplained cardiometabolic benefit requires further study. What's new?: Aromatic and branched‐chain amino acids have been shown to predict both the development of diabetes and cardiovascular disease in several recent epidemiological studies. Some studies have suggested that metformin may alter amino acid concentrations but these studies have been small with a short duration of follow‐up, limiting the inferences that could be made about long‐term treatment. In the CAMERA trial of 173 individuals without diabetes, daily metformin therapy led to sustained reductions in phenylalanine and tyrosine and sustained increases in alanine and histidine concentrations over 18 months.